Portfolio selection with time constraints and a rational explanation of insufficient diversification and excessive trading - Armin Dolzer; Bernhard Nietert (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2006)
Private investors have limited time available for learning about stocks as they need to divide their time between stock analysis and work. This paper analyzes the influence of learning constraintsin the form of time constraints on portfolio selection and derives both optimal portfolio holdings and time allocation. Under time constraints, rational private investors make portfolio choices similar to those ofi nvestors with bounded rationality, i.e., insufficient diversification and excessive trading. Thus, time constraints offer an alternative, fully rational explanation for these real-world investment phenomena, which have to date been interpreted primarily in the light of behavioral finance.
Keywords: G11; G12; 650; excessive trading; insufficient diversification; learning; portfolio selection; time constraint